Network-Assisted Optimal Datalink Selection Scheme for Heterogeneous Aeronautical Network. (16th October 2018) - Wang, Dongli; Huang, Guoce; Dong, Shufu; Wang, Yequn; Liu, Jian; Gao, Weiting
Abstract : Currently, the existing datalink selection algorithms in heterogeneous aeronautical network unilaterally focus on the user side or network side and lack the two sides' cooperation, which seriously affects the utilization of available datalinks. Firstly, to reflect the user-side requirements and network-side load, we propose a user-centric datalink selection scheme combing the user-side multiattribute utility and the network-side access rate for single-user selection. It can be established as a multiobjective optimization problem and solved by the selected optimal datalink. Secondly, for multiuser datalink selection, in order to guarantee the access requests of multiple users, the central control mode of Software Define Networking (SDN) is used to assist the user to perform datalink selection on the network side. By constructing multiuser multiobjective optimization problem, a priority distinction selection (PDS) algorithm is proposed to maximize the number of users accessing their optimal datalinks and minimize the modification of the users' access request. Finally, the proposed user-side datalink selection scheme and network-side assisted selection algorithm are simulated to verify the feasibility and effectiveness.